Validation of single nucleotide polymorphism makers associated with cassava mosaic disease resistance in a clonal evaluation trial - Ishimwe, Y. (University of Ibadan, 2019)
Cassava is an important staple crop in Africa for almost half of the population. The main biotic constraint of the crop is Cassava Mosaic Disease (CMD) which causes significant losses on farmers’ field. The conventional screening for CMD resistance in new cassava populations is time-consuming, expensive and not highly reliable. However, there are newly developed Single Nucleotide Polymorphism (SNP) markers linked to CMD resistance which have not been validated. Therefore, the objective of this research was to validate the reliability and predictive ability of the markers for resistance to CMD. In this study, three SNP markers S12_7926163, S12_7926132, and S14_4626854 were used to genotype a breeding population consisting of 600 accessions from the International Institute of Tropical Agriculture (IITA). This was done by using a Kompetitive Allele-Specific PCR (KASP) approach. These accessions were evaluated on the field using an augmented experimental design of ten blocks with five checks planted randomly and each block had unreplicated single-row plots with five plants each. Assessment of CMD severity was done using a 1-5 scale (1 = Symptomless and 5 = high severity of CMD done at 1 and 3 months after planting and during harvesting at 10 months after planting). Also, data were collected on fresh root weight, shoot weight, and dry matter content. The phenotypic data collected were used to estimate the fresh root yield and harvest index (HI). The data were subjected to correlation analysis and the estimates of variance components, broad-sense heritability as well as linear modeling were best linear unbiased estimates/predictors were derived. Further, a base selection index were used to select the best accessions on their performance to CMD resistance and high fresh root yield. The genotypic data were processed to ensure the quality of the markers by checking the call rates, the minor allele frequency, the proportion of heterozygosity and then to test the accuracy in prediction for all the markers through the marker-trait association. The field screening identified about 75% of the accessions evaluated in this study were resistant to CMD having severity scores of 1 and 2. There was a significant negative correlation (P < 0.001) between CMD severity and yield-related traits which ranged between -0.13 and -0.35. Accession TMS18F1289P0016 had highest DMC of 46 % while accession TMS18F1170P0010 had the least value of 15.4%. Fresh root yield ranged from 1.5 t/ha TMS18F1302P0015 to 43.8 t/ha (TMS15F1367P0001). Harvest index ranged between 0.8 (TMS18F1017P0025) and 0.03 (TMS18F1159P0019). Broad sense heritability estimate for dry matter content, CMD resistance, harvest index, and fresh root yield was 97%, 82%, 40%, and 4.85E-07% respectively. Accession TMS18F1151P0011 had highest SI value (28.24) selected as the accession which has high yield at the same time reistant to CMD. The genotyping results revealed that the call rate of the SNPs was above 95%. The minor allele frequency ranged between 0.3 and 0.4 and the proportion of heterozygosity was more than 0.4. All the SNPs were significantly associated with CMD resistance (p < 0.001). Markers S12_7926132, S12_7926163 and S14_4626854 had prediction accuracy values of 87.5, 87.3 and 62.6%, respectively. The SNP markers evaluated in this study can be reliably used to screen for resistance to cassava mosaic disease.